2011
DOI: 10.1002/pon.1767
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐mediated factors predicting early‐ and late‐stage presentation of breast cancer in Egypt

Abstract: Objective Breast cancer fatality rates are high in low- and middle-income countries because of the late stage at diagnosis. We investigated patient-mediated determinants for late-stage presentation of breast cancer in Egypt. Methods A case–case comparison was performed for 343 women with breast cancer, comparing those who had been initially diagnosed at Stage I or II with those diagnosed at Stage III or IV. Patients were recruited from the National Cancer Institute of Cairo University and Tanta Cancer Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 21 publications
8
60
0
3
Order By: Relevance
“…Many studies linked advanced ages, i.e. seniors, with late presentation (Facione, 1993;Ramirez et al, 1999;Stapleton et al, 2011). This is exactly at odd to our findings that did not correlate both issues.…”
Section: Discussionsupporting
confidence: 67%
“…Many studies linked advanced ages, i.e. seniors, with late presentation (Facione, 1993;Ramirez et al, 1999;Stapleton et al, 2011). This is exactly at odd to our findings that did not correlate both issues.…”
Section: Discussionsupporting
confidence: 67%
“…There must be increased public awareness regarding disease risk factors, symptoms and screening behaviors leading on to the detection of BC at earlier stages. The impact of practising breast screening behaviors on downstaging of BC has been clearly observed in our studies in LMICs [71] .…”
Section: Education and Awareness Enhancement For Improving Bc Outcomessupporting
confidence: 60%
“…In addition, community-level interventions might increase early presentation although the evidence is limited for that [78] . In our studies in other LMICs, we definitely found that increased individual awareness of BSE had a significant impact on early presentation [71] . Increasing awareness also has long term impact on early presentation, as has been suggested by studies in the United Kingdom [79] .…”
Section: Role Of Knowledge and Awareness In Bc Prevention In Lmicssupporting
confidence: 52%
See 1 more Smart Citation
“…[3] Public awareness of breast cancer and its screening had significantly influence its early presentation. [9] Therefore, this study was carried out to assess the knowledge and attitude about breast cancer among women in King Khalid Armed Forces Hospital, Tabuk.…”
Section: Discussion:-mentioning
confidence: 99%